Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1200/jco.2006.10.5411
|View full text |Cite
|
Sign up to set email alerts
|

Survival Prediction in Terminally Ill Cancer Patients by Clinical Estimates, Laboratory Tests, and Self-Rated Anxiety and Depression

Abstract: This study revealed that physicians' survival estimates were unreliable, especially in the case of patients near death. Self-reported emotional distress and objective PFs may improve the accuracy of survival estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
191
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(205 citation statements)
references
References 45 publications
7
191
1
6
Order By: Relevance
“…Christakis et al (2000) reported than only 20% of predictions were accurate and 63% were over-optimistic by a factor of 5.3. Gripp et al (2007) reported similarly that 71-96% of estimates of survival of patients who died within one month were over-optimistic. One head-to-head direct comparison of CPS and prognostic scores in terminally ill patients by Stiel et al (2010) reported lower correlation with actual survival for CPS than for either PPI or PaP.…”
Section: Discussionmentioning
confidence: 97%
“…Christakis et al (2000) reported than only 20% of predictions were accurate and 63% were over-optimistic by a factor of 5.3. Gripp et al (2007) reported similarly that 71-96% of estimates of survival of patients who died within one month were over-optimistic. One head-to-head direct comparison of CPS and prognostic scores in terminally ill patients by Stiel et al (2010) reported lower correlation with actual survival for CPS than for either PPI or PaP.…”
Section: Discussionmentioning
confidence: 97%
“…The main indicators of this final phase are poor performance status; weight loss; symptoms such as appetite loss, breathlessness, or confusion; and abnormalities on some laboratory parameters, including high white cell count, lymphopenia, hypoalbuminemia, and elevated lactate dehydrogenase or C-reactive protein. 4,5,13 Recently, a two-week survival prognostic model that incorporated both biochemical markers and the presence of appetite loss, dyspnea, and edema 14 was used in a palliative care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stressors may be responsible for cognitive complaints, especially in the domain of memory, which could have a role in diminishing treatment compliance 107 . However, at a mechanistic level, mounting evidence indicates that chronic stress confer increased vulnerability to chronic diseases amplifying pro-inflammatory signals via an increased production of cytokines and other immune mediators, as well as via a decreased sensitivity to hormonal inhibitory control by the HPA axis, as well altered autonomic responses 108,109 .…”
Section: Stress As a Modulator Of Immune Response In Depression And Cmentioning
confidence: 99%